2021
DOI: 10.3904/kjim.2020.325
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of viral load and anti-SARS-CoV-2 antibodies in patients with positive RT-PCR results after recovery from COVID-19

Abstract: Recently, the number of patients with coronavirus disease 2019 (COVID-19) who have tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), via the reverse transcription polymerase chain reaction (RT-PCR) test, after recovery has increased; this has caused a dilemma regarding the medical measures and policies. We evaluated the dynamics of viral load and anti-SARS-CoV-2 antibodies in four patients with positive RT-PCR results after recovery. In all patients, the highest levels of immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 8 publications
0
34
0
Order By: Relevance
“…No close contacts or family members were infected. The first time positive Ct value upon hospitalization and second time positive Ct value after discharge, showed no significant difference Zhang et al [77] China Case report 3 1 36,54,50,55 4/- 15 d,25 d,6 d,15 d positive 4 IgG positive 3 IgM positive All presented with no symptoms, and the chest CT scan of three cases was normal Song et al [69] Korea Case report 3 1 73,33,31,18 month 4/- 4 d,9 d,9 d,9 d positive positive In 4 RP patients, the highest levels of IgG and IgM antibodies were reached after about a month of the onset of the initial symptoms. Then, the IgG titers plateaued, and the IgM titers decreased, regardless of RT-PCR results.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…No close contacts or family members were infected. The first time positive Ct value upon hospitalization and second time positive Ct value after discharge, showed no significant difference Zhang et al [77] China Case report 3 1 36,54,50,55 4/- 15 d,25 d,6 d,15 d positive 4 IgG positive 3 IgM positive All presented with no symptoms, and the chest CT scan of three cases was normal Song et al [69] Korea Case report 3 1 73,33,31,18 month 4/- 4 d,9 d,9 d,9 d positive positive In 4 RP patients, the highest levels of IgG and IgM antibodies were reached after about a month of the onset of the initial symptoms. Then, the IgG titers plateaued, and the IgM titers decreased, regardless of RT-PCR results.…”
Section: Resultsmentioning
confidence: 93%
“…Nineteen studies ( n = 101) [ 16 , 18 , 22 – 25 , 32 , 35 , 36 , 49 – 51 , 59 , 73 , 76 , 97 , 104 , 107 , 115 ] showed that discharged patients had no symptoms when the nucleic acid test was positive. Among 55 studies, 1054 RP patients had symptoms, cough (19·82%) [ 20 , 26 , 29 – 31 , 34 , 38 , 42 , 44 , 49 , 52 , 60 , 62 , 63 , 66 , 67 , 69 , 71 , 74 , 78 , 81 , 83 85 , 88 , 89 , 91 , 94 , 95 , 98 , 101 , 103 , 106 , 108 , 110 , 119 , 121 , 125 , 127 , 130 ] and fever (14·99%) [ 20 , 28 , 29 , 41 , 44 , 46 , 49 , 52 , 67 ,…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, some patients with recurrence may produce lower specific antibody titres in comparison to those without recurrence, suggesting that the virus may not confer immunity sufficiently due to limited antibody levels and after that causes recurrence [ 46 , 48 ]. In a case series study, a 33-year old man who experienced recurrence two times did not develop IgM ever during the follow-up period [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this context, RT-PCR assay was useful for the detection of SARS-CoV-2 in these decomposed samples while other methods including histopathology, and high-resolution computed tomography (HRCT), blood examination etc., have limitations. However, RT-PCR, being a very sensitive and genome-based technique can show positive with the mere presence of traces of fragmented genome, which is observed in samples of asymptomatic and recovered subjects[26]. Additionally, findings from this assay might not reveal if the virus was viable or dead in the decomposed tissue but demonstrate the stability of the SARS-CoV-2 genome in the decomposed tissue.…”
Section: Resultsmentioning
confidence: 99%